Regular Nonsteroidal Anti‐Inflammatory Drug Use Increases Stress Fracture Risk in the General Population: A Retrospective Case‐Control Study - Ciuciu, Alexandra; Mulholland, Christopher; Bozzi, Michael A.; Frymoyer, Chris C.; Cavinatto, Leonardo; Yaron, David; Harwood, Marc I.; Close, Jeremy D.; Mehallo, Christopher J.; Tomlinson, Ryan E. (Advances in orthopedics, 2024)
Previous studies have shown that the use of nonsteroidal anti‐inflammatory drugs (NSAIDs) is associated with increased stress fracture risk. This phenomenon has been studied predominantly in high‐activity individuals, so data regarding the general population are limited despite the substantial economic and resource burden of stress fracture injuries within the general US population. Furthermore, our preclinical studies demonstrate that regular use of NSAIDs also diminishes the intrinsic ability of bone to resist fracture. To determine the association of regular NSAID use with stress fractures in the general population, we surveyed subjects presenting with either stress fracture or uncomplicated ankle sprain to assess their use of NSAIDs over the three months before their injury. We hypothesized that subjects with stress fractures would have increased regular NSAID usage as compared to controls. Subjects diagnosed with a stress fracture ( n = 56) and subjects with uncomplicated ankle sprains ( n = 51; control) were surveyed about their NSAID use at the time of their diagnosis and in the previous three months using a questionnaire based on the National Health and Nutrition Examination Survey (NHANES). Subjects were surveyed in person on the day of their injury diagnosis or by phone within 30 days of their diagnosis. Fisher’s exact test was used to determine significant differences in NSAID usage between stress fracture and control subjects. Subjects diagnosed with stress fractures had a statistically significant increase in both current use ( p = 0.03) and regular use ( p = 0.04) of ibuprofen/naproxen/celecoxib as compared to control subjects. There were no significant differences in the use of aspirin, acetaminophen, or prescription medications containing acetaminophen between groups. Consistent with previous clinical reports, we observed a strong correlation between regular ibuprofen/naproxen/celecoxib use and stress fracture incidence in the general population. These results indicate that patients at high risk of stress fracture should avoid regular use of ibuprofen, naproxen, or celecoxib.